Analisis Spasial Upah Minimum Kabupaten/Kota di Provinsi Jawa Tengah Tahun 2017-2021 dengan Model SAR-RE - Adham Malay Japany; Annisa Firnanda (Seminar Nasional Official Statistics, 2022)
As remuneration for labor, the compensation given is usually in the form of wages or salaries. In maintaining wage stability, a minimum wage is established. The similarity of the Regency/City Minimum Wage (UMK) in Central Java Province is inseparable from the spatial effect. Thus, this study aims to identify the spatial effect and determine the variables that affect the UMK in Central Java Province. The data used in this study is secondary data from the Central Java BPS website with 35 regencies/cities of observation in 2017-2021. The best model used is Spatial Autoregressive Random Effect (SAR-RE). The test results show that there are three significant variables, namely the ADHK GDP and HDI variables that have a positive effect, and the variable of expenditure per capita that has a negative effect. In addition, the UMK in an area also has a positive and significant effect on the surrounding UMK, while TPAK has no effect on the UMK in Central Java Province in 2017-2021.